Impact of processing conditions and gelling agent on physical and sensorial properties of pecan oil-dulce de leche gummy candies - Ranalli, Natalia (2020)
For the development of gelatinized dairy products that include emulsified pecan oil as an unsaturated fatty acid source the incorporation of hydrocolloids becomes necessary and their properties must be carefully selected. This work aimed to study gelatinized candies made with 0% milk fat dulce de leche with pre-emulsified pecan nut oil using combinations of gelatin (4.67 to 7 g/100 g) and high methoxyl pectin (1.33 to 2 g/100 g) as gelling agents. The effect of different drying methods (vacuum-oven at 35 °C for 24 h and freeze-drying) was evaluated. Control samples without drying were also studied. Dehydration conditions significantly (p < 0.05) affected aw, texture (hardness, cohesiveness, adhesiveness, gumminess, springiness, and resilience) and color parameters (L*, a*, b*) of products, being higher than the effect of the gelling agent. Formulations were selected based on texture and aw criteria and sensory evaluated by appearance, color, texture, taste, and overall acceptability. Two formulations (one with 7% gelatin and 1.33% high methoxyl pectin content, and the other with 2% high methoxyl pectin and 4.67% gelatin content), both with low moisture content and vacuum-dried, exhibited good acceptability. These pecan oildulce de leche gummy candies would represent a healthier candy version, low in saturated fatty acids, and source of oleic acid.